Examination of the acute efficacy and safety about aggressive use of tolvaptan for early rising after admission in super-elder patients with congestive heart failure. (14th October 2021) - Takaishi, A; Iida, T; Kishinoue, T; Mori, H; Yamaji, T; Tanimoto, M; Onishi, N; Hirohata, S; Ueeda, M; Ito, H
Abstract: Background: From August 2015, for shortening of hospitalization period through efficient medical care in acute phase, we had introduced a unique clinical pathway (PATH) for congestive heart failure (CHF) cases. In PATH, since immediate taking of Tolvaptan, which is an strong oral diuretic and approver for use in the treatment of CHF cases since 2010 in Japan, after admission is specified, early diuresis makes it possible to achieve early rising from bed and streamline each medical care such as oxygen inhalation, continuous infusion, and urethral catheterization. Early rising from bed is particularly important for super-elder CHF patients who merge often frail. On the other hand, for super-elder CHF patients, it is feared that aggressive use of Tolvaptan may frequently cause dehydration, renal damage caused by it, or hypernatremia, which is a peculiar side effect about the drug. Purpose: In this study, we examined the usefulness and safety of active use of Tolvaptan by introducing PATH in patients with super-elder CHF patients. Methods: We set up three groups, NE group consist of 37 CHF cases (90 years old or over) who admitted in our hospital before (without) introduction of PATH between April 2014 and July 2015, PE group consist of 130 CHF cases (90 years old or over) and PY group consist of 466 CHF cases (under 90 years old) who ware admitted with introduction of PATH between August 2015 and July 2020. And in each group, we investigated various medical conditions in their acute phase after admission and the incidence of adverse events related to oral administration of tolvaptan, and examined the differences between three groups. Results: Between NE group and PE group, there were no significant differences in mean age, pre-hospital living status, or clinical status at admission (Figure 1). But due to lean and efficient CHF care, the average length of hospitalization period was significantly shorter in PE group. And, in PE group, each medical care was performed as efficiently as in PY group, but the progression of renal damage or hypernatremia that required unscheduled discontinuation of tolvaptan use occurred more frequently in PE group (Figure 2). Conclusions: Aggressive Tolvaptan use through our unique clinical pathway for congestive heart failure cases seemed to be useful even in super-elder patients. Although we thought that the safety of active use of tolvaptan for super-elder patients was well tolerated considering the results of this study, the incidence of adverse events such as hypernatremia was clearly higher in super-elder patients than in non-super-elder patients. It seemed that we should pay close attention to the clinical data of super-elder patients after introduction of tolvaptan. Funding Acknowledgement: Type of funding sources: None.